The Correlation Between Students’ Vocabulary Mastery And Speaking Skill - Dano, Rizqika Fajriah; Waris, Ahmad Mustamir; Komariah, Anis (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2022)
This research aimed to determine whether there is a correlation between students’ vocabulary mastery and their speaking skills. The subjects were 40 students from eleventh-grade students (XI MIPA 2) of MAN Model 1 Manado. The design that was applied in this research was the quantitative method. The data gained in this research by giving the students speaking and vocabulary test then analyzed using the Pearson product-moment correlation formula. Based on the finding of the analysis and calculation, it was found that the rxy was 0,799. Referring to the table of product-moment interpretation, it was in the interval of 0,70 - 0,90, which means that variables X and Y stated a high correlation. According to the significance table, the degree of freedom (df = N-nr) is 38, the significance level 5% is 0,320, and 1% is 0,413. Comparing the values showed that rxy is bigger than rt (0,320<0,799>0,413). It means there is a significant correlation between vocabulary mastery and speaking skills, which proves that students’ vocabulary mastery increases in line with their speaking skills.